Reabilitação de Bairros e Arquitectura. Estratégias de processo; Práticas de projecto. (SAAL/NORTE: 1974-1976/1997, 2012) - José Alberto Abreu Lage (2017)
Starting from an approach which moves and identifies itself in the problems exposed in this thesis; in the reading of the genetic code of the degraded landscape in analysis; in the survey and understanding of the "utopia of the SAAL process"; in the study of one sector - the oriental one - of Porto, we look forward to pointing out ways for the construction of an alarm project of development, of urban requalification. A "project" founded on the preexisting structures, which, including the inhabitant, with this one may balance and activate making evolving other material conditions for his quality of life. A "project" which, dynamized in real conditions of experience, may liberate-dynamize other situations of effective "circumstance-of-project" in the city. Through the prior recognition of the specificity of landscape, initially worked by the SAAL/Norte process, in Porto, it is possible to prospect contributions or models of intervention that will allow the establishing of premises for the valuation of the people and the territory they inhabit, of the city and architecture, of the landscape and heritage, intrinsic to the imperatives of urban development.